Kajian terhadap Faktor-Faktor yang Memengaruhi Tingkat Kesiapan Pegawai untuk Berubah - Zuvita Syafril (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2022)
A rapidly changing environment requires organizations and individuals to be able to adapt to make changes. Political, economic, social, technological or environmental developments have forced public organizations to continuously adapt to changing circumstances, so that organizations are in a continuous cycle of organizational change. Employees have an important role in implementing various change initiatives in the organization. Previous research has recognized the important role of employee readiness to change in implementing organizational change. This study aims to examine several factors related to readiness for change such as high-perfomance human resource management practices, affective commitment, and organizational identification. This research involves 251 respondents who are permanent employees at one of the Supervisory and/or Regulatory Institutions in Indonesia. The collected data were analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) method with the AMOS application. The results of the study show that high-performance human resource management practices have a positive and significant effect on affective commitment, organizational identification, and employee readiness to change. This research provides insights for practitioners in the public sector on how to increase readiness to change employees through optimizing high-performance human resource management practices.